The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s12981-017-0148-9
|View full text |Cite
|
Sign up to set email alerts
|

What influences quality of life in older people living with HIV?

Abstract: BackgroundPeople with HIV with access to treatment are growing older and living healthier lives than in the past, and while health improvements and increased survival rates are welcome, the psychological and social consequences and quality of life of ageing are complex for this group. Understanding how ageing, HIV and quality of life intersect is key to developing effective interventions to improve QoL.MethodsOne hundred people with HIV over the age of 50 (range 50–87, mean 58), were recruited through HIV comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 27 publications
3
21
0
1
Order By: Relevance
“…For example, HIV stigma made it difficult to establish romantic or sexual relationships, which was especially evident among gay men, many of whom also had to contend with homonegativity. This is important, as previous research has demonstrated that being in a relationship can improve the quality of life among older persons with HIV (Catalan et al ., 2017) and successful ageing with HIV often includes deliberately creating social networks that promote resilience and positivity (Emlet, 2017). Yet, for many in this study, their rural environment and social isolation was such that they had few options for social support, much less romantic or sexual relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, HIV stigma made it difficult to establish romantic or sexual relationships, which was especially evident among gay men, many of whom also had to contend with homonegativity. This is important, as previous research has demonstrated that being in a relationship can improve the quality of life among older persons with HIV (Catalan et al ., 2017) and successful ageing with HIV often includes deliberately creating social networks that promote resilience and positivity (Emlet, 2017). Yet, for many in this study, their rural environment and social isolation was such that they had few options for social support, much less romantic or sexual relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Rooted in intersectionality theory, intersectional stigma can help explain how persons simultaneously experience multiple stigmas and how such stigmas affect social, mental and physical wellbeing (Logie et al ., 2011). Intersectional stigma, and its manifestations and consequences, can contribute to poor quality of life in older people living with HIV (Catalan et al ., 2017). Older adults living with HIV are often subject to the intersecting stigmas of ageism and HIV stigma, and some may also have to contend with racism and/or homonegativity, the combination of which may multiply the negative effects on their mental health and access to social support (Emlet et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In China, the prevalence of depressive symptom was 74.2% among older PLWH [8], the rate is higher than that of their younger counterparts [8,[11][12][13], due to age-related reduction in immune responses, impaired physical function, reduced social support, or difficulties in coping with HIV-related stress [8,14]. Therefore, more attention should be given to this older PLWH [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Four participants did not fall neatly within our three core participant groups: one White bisexual woman and one Black African women of unknown sexual orientation, whose interviews and survey data we analysed, and one heterosexual man and one heterosexual woman of Black Caribbean heritage, whom we excluded from qualitative analysis while retaining their survey data, which are not shown here (for survey data analysis and findings, see Rosenfeld et al , 2015; Catalan et al ., 2017). We stopped recruiting after preliminary analysis achieved theoretical saturation (Charmaz, 2014).…”
Section: Methods and Samplementioning
confidence: 99%
“…As people living with HIV (PLWH) age following the introduction of effective antiretroviral therapy in 1996 (Sabin, 2013), which changed HIV from a typically fatal condition to a potentially long-term manageable one, research into the social dimensions of ageing with HIV is growing (Emlet, 2006 a , 2008; Wallach and Brotman, 2013; Nevedal and Sankar, 2015; Hutton, 2016; Furlotte and Schwartz, 2017; Catalan et al ., 2017; Wallace and Brotman, 2017). Much of this research documents the distinctive challenges that ageing introduces to the experience of living with HIV (within the HIV context, the term ‘older’ refers to those aged 50 and above; see e.g.…”
Section: Introductionmentioning
confidence: 99%